دراسة تحليلية لفاعلية حراس المرمى لأقوى منتخبات كأس العالم 2022 بقطر - سهلي أنيس (My University, 2023)
................................................................................................abstract............................................... Study title: An analytical study of the effectiveness of goalkeepers for the strongest teams in the World Cup Qatar 2022. Purpose of the study: •. An analytical study of the effectiveness of goalkeepers for the strongest teams in the World Cup Qatar 2022. Identify the differences in the level of performance of goalkeepers for tackles from framed shots and long passes using modern technology. The problem of the study: - Does the use of modern technology give us good results to evaluate the effectiveness of the goalkeeper performance of the strongest teams that reached the final in the Qatar World Cup 2022? Included within this general question are the following partial questions or problems: 1- Does the use of modern technology give us good results to evaluate the effectiveness of goalkeeper performance in terms of saves? 2- Does the use of modern technology give us good results to evaluate the effectiveness of goalkeeper performance in terms of accurate passes? Study hypotheses: The general hypothesis: The use of modern technology gives us accurate results to evaluate the effectiveness of goalkeeper performance for the strongest teams that reached the final in the Qatar World Cup 2022. Partial hypotheses: - The use of modern technology gives us accurate results to evaluate the effectiveness of goalkeeper performance in terms of tackles. - The use of modern technology gives us accurate results to evaluate the effectiveness of the goalkeeper's performance in terms of accurate passes. The study sample: the matches of the sixteenth round, the quarter-finals, the semi-finals, the third place, and the final of the 2022 World Cup in Qatar for the goalkeepers of the following teams: (Argentina, Croatian, Moroccan, French), and the total number of matches was 12. The method used in the study: the descriptive analytical method. Study tools: - The researcher used modern technology to evaluate the players and an observation form to record and collect information. Statistical methods: We used the method of statistical analysis, which enables us to count all the correct tackles and passes, then write them in a table after converting them into percentages, and also using the effectiveness index in addition to k squared (k2). Average percentage of tackles and accurate passes Average rating. Conclusions and suggestions: Conclusions:  Proving the validity of the hypothesis that the use of modern technology gives us accurate results to evaluate the effectiveness of goalkeeper performance for the strongest teams in the Qatar World Cup 2022.  In the sixteenth round, there are no statistical differences in the saves.  In the quarter-finals, there are statistical differences for the greatest value in the responses of the Croatian goalkeeper.  In the semi-final round, there are statistical differences for the greatest value in the responses of the Croatian goalkeeper.  Third place role There are no statistical differences in responses.  Final round There are no statistical differences in responses.  Statistical results for the average percentage of saves, we find that the best goalkeeper of Croatia Dominik Livakovic.  Statistical results for the average evaluation of saves, we find that the best goalkeeper of Croatia Dominik Livakovic..  Performance fluctuations: Although goalkeepers can show fluctuations in their performance throughout the different phases, they generally performed well in the Qatar World Cup 2022. This indicates a high ability to adapt and deal with the pressures of competing in the World Championship.   Confidence and influence: Confidence and good communication with other players may be one of the factors affecting achieving successful responses and maintaining positive results. Suggestions: - We recommend football federations to use modern technologies to evaluate the performance level of players, especially goalkeepers. - Analysis of influencing factors: The study can be expanded to analyze the factors influencing the performance of goalkeepers more accurately. These factors may include the tactical system of the team, the level of defense, individual and collective confidence, and the psychological pressure that goalkeepers face in big matches. - Statistical analysis models can be used to apply predictive models of goalkeepers' performance and link them to modern technologies to evaluate the players' performance level. - The basic rules for good performance can be determined using modern techniques to evaluate the level of performance of goalkeepers and players and to explore weaknesses and points of improvement. Individual and team performance evaluation: Group performance and the interaction between goalkeepers, the defensive line and the rest of the players on the team can also be analyzed. Studying tactics and strategies: Tactics and strategies used by teams and their impact on goalkeeper performance can be analyzed. There may be strategies for defence, organization and communication between the goalkeepers and the backline that can influence goalkeeper performance directly .........................................................................................................الملخص........................................................................................................... عنوان الدراسة: دراسة تحليلية لفاعلية حراس المرمى لأقوى منتخبات كأس العالم قطر 2022. هدف الدراسة: •. دراسة تحليلية لفاعلية حراس المرمى لأقوى منتخبات كأس العالم قطر 2022. •التعرف على الفروق في مستوى أداء حراس المرمى للتصديات من التسديدات المؤطرة والتمريرات الطويلة باستخدام التقنية الحديثة . مشكلة الدراسة: - هل استخدام التقنية الحديثة تعطينا نتائج جيدة لتقييم فاعلية أداء حراس المرمى لأقوى المنتخبات الواصلة الى النهائي في كاس العالم قطر2022؟ ويندرج ضمن هذا التساؤل العام التساؤلات أو الإشكاليات الجزئية التالية: 1- هل استخدام التقنية الحديثة تعطينا نتائج جيدة لتقييم فاعلية أداء حراس المرمى من ناحية التصديات ؟ 2- هل استخدام التقنية الحديثة تعطينا نتائج جيدة لتقييم فاعلية أداء حراس المرمى من ناحية التمريرات الدقيقة؟ فرضيات الدراسة: الفرضية العامة: ان استخدام التقنية الحديثة تعطينا نتائج دقيقة لتقييم فاعلية أداء حراس المرمى لأقوى المنتخبات الواصلة الى النهائي في كاس العالم قطر2022. الفرضيات الجزئية: - ان استخدام التقنية الحديثة تعطينا نتائج دقيقة لتقييم فاعلية أداء حراس المرمى من ناحية التصديات. - ان استخدام التقنية الحديثة تعطينا نتائج دقيقة لتقييم فاعلية أداء حراس المرمى من ناحية التمريرات الدقيقة. عينة الدراسة: مباريات الدور السادس عشر والربع النهائي والنصف نهائي والمركز الثالث ونهائي كأس العالم 2022 بقطر لحراس مرمى المنتخبات التالية:( الأرجنتيني، الكرواتي، المغربي، الفرنسي) وكانت مجموع المباريات 12. المنهج المتبع في الدراسة: المنهج الوصفي التحليلي. أدوات الدراسة: - استخدم الباحث التقنية الحديثة لتقييم اللاعبين واستمارة ملاحظة لتدوين وجمع المعلومات. الأساليب الإحصائية: استخدمنا طريقة التحليل الإحصائي التي تمكن من إحصاء جميع التصديات و التمريرات الصحيحة ثم كتابتها في جدول بعد تحويلها الى نسب مئوية و أيضا باستعمال مؤشر الفاعلية بالإضافة الى ك التربيع (ك2) - متوسط النسب التصديات و التمريرات الدقيقة - متوسط التقييم. الإستنتاجات و الإقتراحات: - الإستنتاجات:  إثبات صحة الفرضية بأن استخدام التقنية الحديثة تعطينا نتائج دقيقة لتقييم فاعلية أداء حراس المرمى لأقوى منتخبات كأس العالم قطر2022.  في دور السادس عشر لا توجد فروق إحصائية في التصديات.  في الدور الربع النهائي توجد فروق إحصائية لأكبر قيمة في التصديات للحارس الكرواتي.  في الدور النصف النهائي توجد فروق إحصائية لأكبر قيمة في التصديات للحارس الكرواتي.  دور المركز الثالث لا توجد فروق إحصائية في التصديات.  دور النهائي لا توجد فروق إحصائية في التصديات.  النتائج الإحصائية لمتوسط نسب التصديات نجد أن أفضل حارس كرواتيا Dominik Livakovic.  النتائج الإحصائية لمتوسط تقييم التصديات نجد أن أفضل حارس كرواتيا Dominik Livakovic..  تقلبات الأداء: على الرغم من أن حراس المرمى يمكن أن يظهروا تقلبات في أدائهم عبر المراحل المختلفة، إلا أنهم قدموا أداءً جيدًا بشكل عام في كأس العالم قطر 2022. هذا يدل على وجود قدرة عالية للتأقلم والتعامل مع ضغوط المنافسة في بطولة العالم.  الثقة والتأثير : قد تكون الثقة والتواصل الجيد مع اللاعبين الآخرين أحد العوامل المؤثرة في تحقيق تصديات ناجحة وحفاظا على النتائج الإيجابية. - الإقتراحات: - نوصي إتحادات كرة القدم باستخدام التقنيات الحديثة منها لتقييم مستوى أداء اللاعبين خاصة حراس المرمى. - تحليل العوامل المؤثرة: يمكن توسيع الدراسة لتحليل العوامل المؤثرة في أداء حراس المرمى بشكل أكثر دقة. قد تشمل هذه العوامل النظام التكتيكي للفريق، مستوى الدفاع، الثقة الفردية والجماعية، والضغط النفسي الذي يواجهه الحراس في المباريات الكبيرة. - يمكن استخدام نماذج التحليل الاحصائي لتطبيق نماذج تنبؤية لأداء الحراس المرمى وربطها بالتقنيات الحديثة لتقييم مستوى أداء اللاعبين. - يمكن تحديد القواعد الأساسية للأداء الجيد باستخدام التقنيات الحديثة لتقييم مستوى أداء حراس المرمى و اللاعبين واستكشاف الضعف ونقاط التحسين. -تقييم الأداء الفردي والفرقي: يمكن أيضًا تحليل الأداء الجماعي والتفاعل بين حراس المرمى وخط الدفاع وباقي اللاعبين في الفريق. -دراسة التكتيكات والاستراتيجيات : يمكن تحليل التكتيكات والاستراتيجيات التي تستخدمها المنتخبات وتأثيرها على أداء حراس المرمى. قد تكون هناك استراتيجيات خاصة بالدفاع والتنظيم والتواصل بين الحراس وخط الدفاع يمكن أن تؤثر على أداء حراس المرمى بشكل مباشر ..............................................................................................................................résumé............................................................................... Titre de l'étude : Une étude analytique de l'efficacité des gardiens de but pour les équipes les plus fortes de la Coupe du monde Qatar 2022. But de l'étude: •. Une étude analytique de l'efficacité des gardiens des équipes les plus fortes de la Coupe du Monde Qatar 2022. Identifiez les différences de niveau de performance des gardiens de but pour les tacles à partir de tirs cadrés et de longues passes à l'aide de la technologie moderne. Le problème de l'étude : - L'utilisation de la technologie moderne nous donne-t-elle de bons résultats pour évaluer l'efficacité de la performance des gardiens des équipes les plus fortes qui ont atteint la finale de la Coupe du monde de Qatar 2022 ? Cette question générale comprend les questions ou problèmes partiels suivants : 1- L'utilisation de la technologie moderne nous donne-t-elle de bons résultats pour évaluer l'efficacité de la performance du gardien en termes d'arrêts ? 2- L'utilisation de la technologie moderne nous donne-t-elle de bons résultats pour évaluer l'efficacité des performances du gardien en termes de passes précises ? Hypothèses d'étude : L'hypothèse générale : L'utilisation de la technologie moderne nous donne des résultats précis pour évaluer l'efficacité des performances des gardiens de but pour les équipes les plus fortes qui ont atteint la finale de la Coupe du monde de Qatar 2022. Hypothèses partielles : - L'utilisation de la technologie moderne nous donne des résultats précis pour évaluer l'efficacité des performances du gardien de but en termes de tacles. - L'utilisation de la technologie moderne nous donne des résultats précis pour évaluer l'efficacité de la performance du gardien de but en termes de passes précises. L'échantillon d'étude : les matchs du seizième tour, les quarts de finale, les demi-finales, la troisième place et la finale de la Coupe du monde 2022 au Qatar pour les gardiens des équipes suivantes : (Argentine, Croate, Marocain, français), et le nombre total de matchs était de 12. La méthode utilisée dans l'étude : la méthode analytique descriptive. Outils d'étude : - Le chercheur a utilisé la technologie moderne pour évaluer les joueurs et un formulaire d'observation pour enregistrer et collecter des informations. Méthodes statistiques : Nous avons utilisé la méthode d'analyse statistique, qui permet de compter tous les tacles et passes corrects, puis de les écrire dans un tableau après les avoir convertis en pourcentages, et aussi d'utiliser l'indice d'efficacité en plus de k au carré (k2). Pourcentage moyen de tacles et de passes précises Note moyenne. Conclusions et suggestions : Conclusion :  Prouver la validité de l'hypothèse selon laquelle l'utilisation de la technologie moderne nous donne des résultats précis pour évaluer l'efficacité des performances des gardiens de but pour les équipes les plus fortes de la Coupe du monde du Qatar 2022.  Au seizième tour, il n'y a pas de différences statistiques dans les arrêts.  En quart de finale, il y a des différences statistiques pour la plus grande valeur dans les réponses du gardien croate.  En demi-finale, il y a des différences statistiques pour la plus grande valeur dans les réponses du gardien croate.  Rôle de troisième place Il n'y a pas de différences statistiques dans les réponses.  Tour final Il n'y a pas de différences statistiques dans les réponses.  Résultats statistiques pour le pourcentage moyen d'arrêts, nous constatons que le meilleur gardien de la Croatie Dominik Livakovic.  Résultats statistiques pour l'évaluation moyenne des arrêts, nous constatons que le meilleur gardien de but de la Croatie Dominik Livakovic..  Fluctuations des performances : bien que les gardiens de but puissent montrer des fluctuations dans leurs performances tout au long des différentes phases, ils ont généralement bien performé lors de la Coupe du monde du Qatar 2022. Cela indique une grande capacité à s'adapter et à faire face aux pressions de la compétition dans le Championnat du monde.   Confiance et influence : La confiance et une bonne communication avec les autres joueurs peuvent être l'un des facteurs affectant l'obtention de réponses réussies et le maintien de résultats positifs. Suggestions: - Nous recommandons aux fédérations de football d'utiliser les technologies modernes pour évaluer le niveau de performance des joueurs, en particulier des gardiens de but. - Analyse des facteurs influents : L'étude peut être élargie pour analyser plus précisément les facteurs influençant la performance des gardiens de but. Ces facteurs peuvent inclure le système tactique de l'équipe, le niveau de défense, la confiance individuelle et collective et la pression psychologique à laquelle les gardiens sont confrontés lors des grands matches. - Des modèles d'analyse statistique peuvent être utilisés pour appliquer des modèles prédictifs de la performance des gardiens de but et les relier aux technologies modernes pour évaluer le niveau de performance des joueurs. - Les règles de base pour une bonne performance peuvent être déterminées en utilisant des techniques modernes pour évaluer le niveau de performance des gardiens de but et des joueurs et pour explorer les faiblesses et les points d'amélioration. Évaluation des performances individuelles et d'équipe : Les performances de groupe et l'interaction entre les gardiens de but, la ligne défensive et le reste des joueurs de l'équipe peuvent également être analysées. Étudier les tactiques et les stratégies : Les tactiques et les stratégies utilisées par les équipes et leur impact sur les performances du gardien de but peuvent être analysées. Il peut y avoir des stratégies de défense, d'organisation et de communication entre les gardiens de but et la ligne de fond qui peuvent influencer directement la performance du gardien de but
- ابتداء من الدور السادس عشر لكأس العالم 2022 بقطر -